Strategi Pengembangan Pasar Tradisional di Kota Semarang - Bani Astiti Asa Nugroho; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Traditional Market is a favorite place for people, especially the low and middle class to buy the daily needs. Traditional Market has a characteristic, which is the bidding process. Traditional markets in Semarang is one contributor to PAD through the levy and able to absorb a lot of labor as seller’s market, pedicab drivers, parking attendants and porters. Currently there are 44 traditional markets in the Semarang. The purpose of this research is to identify factors supporting and obstructing the development of traditional markets in Semarang and formulate the strategy of development traditional markets in Semarang. This research uses qualitative descriptive method by using informant from the Department of Market in Semarang, traditional market seller and the public as a visitor the traditional market in the Semarang. The analysis process begins with identifying the internal and external environment of Department of Market in Semarang using the SWOT analysis to obtain the issues of strategy and then measured by Litmus test. Results of the research strategy of development traditional markets in Semarang City through SWOT analysis contained eight Issues Strategy. Based on the results of litmus test, strategy of development traditional market with the highest score are Optimalizing development and revitalization of traditional markets include ease of access for society and seller and development of traditional markets by utilizing the potential and characteristics.